Peningkatan Mutu dan Kualitas Pendidikan dengan Membangkitkan Tiga Potensi Dasar Alamiah (Bayu, Sabda, Idep) - I Putu Gede Parmajaya (Jurnal Penjaminan Mutu, 2015)
The low quality and the quality of education in Indonesia is not a secret anymore. Even among ASEAN countries alone, the quality of education in Indonesia arriving under Singapore, Thailand, Vietnam and even Filiphine. Issue low quality of education in Indonesia has often been a hot topic in various scientific forums, discussion will be the condition of education in Indonesia. Many efforts have been taken by the government with the enactment of Law No. 20 of 2003 on the National Education System, but it has not been able to resolve the problem of the quality of education in Indonesia. Today the efforts to improve the quality of education being conducted by various parties. These efforts based on an awareness of the importance of the role of education in the development of human resources and the development of national character (Nation Character Building) for the betterment of society and the nation. Dignity of a nation is determined by the quality of education. The way is to raise three potential natural base (word, wind, eyelash) humans.